2007
DOI: 10.1111/j.1524-4741.2007.00400.x
|View full text |Cite
|
Sign up to set email alerts
|

Flare-up of Dermatomyositis Along with Recurrence of Breast Cancer

Abstract: n Abstract: Dermatomyositis is an idiopathic inflammatory myopathy with characteristic cutaneous manifestations. The association between dermatomyositis and malignancy is becoming more clearly delineated. A sort of dermatomyositis is thought to be paraneoplastic syndrome and dermatomyositis may follow clinical course of malignancy. We report a 68-yearold woman with dermatomyositis, whose clinical onset of dermatomyositis was apparently concomitant with breast cancer. Dermatomyositis had settled down and oral s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…Few studies reported recurring cases of DM and other cancers. These reports demonstrated the association between DM symptoms and cancer recurrence in patients with ovarian cancer [15], breast cancer [16], and bladder cancer [17], supporting our findings in colorectal cancer. The present report describes a rare case with a good outcome of resecting liver metastases that were detected early by exacerbation of skin symptoms before annual examination in a patient with DM accompanied by rectal cancer.…”
Section: Discussionsupporting
confidence: 88%
“…Few studies reported recurring cases of DM and other cancers. These reports demonstrated the association between DM symptoms and cancer recurrence in patients with ovarian cancer [15], breast cancer [16], and bladder cancer [17], supporting our findings in colorectal cancer. The present report describes a rare case with a good outcome of resecting liver metastases that were detected early by exacerbation of skin symptoms before annual examination in a patient with DM accompanied by rectal cancer.…”
Section: Discussionsupporting
confidence: 88%
“…It has also been observed that myopathy may relapse in the setting of recurrent malignancy, further supporting a paraneoplastic origin of malignancy-associated DM 10 12. This suggests that appropriate clinical follow-up of patients previously diagnosed with malignancy-associated DM should include observation for evidence of recurrent malignancy as well as for symptoms and signs of recurrent myopathy.…”
Section: Discussionmentioning
confidence: 94%
“…No trends in hormone receptor status were observed in these breast cancer patients with dm. The distribution of triple-negative 8,18 , her2-positive 9,10,12,15,16 , and estrogen or progesterone receptor-positive [12][13][14]16,17 breast cancers was relatively even.…”
Section: Discussionmentioning
confidence: 98%
“…Most patients were diagnosed with cancer before they were diagnosed with dm; only 6 of the 25 (24%) presented with myositis symptoms first 13,18,19 . The presence of dm was associated with late-stage tumours, 72% of the women (18 of the 25) having presented with stage iii or iv disease 9,10,[12][13][14][15][16][17][18]20 . No trends in hormone receptor status were observed in these breast cancer patients with dm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation